Can't stop won't stop : a hip-hop history - Chang, Jeff; Davey D, 1970- (Wednesday Books, 2021)
"The American Book Award winner, now completely adapted for a young adult audience! From award-winning author Jeff Chang, Can't Stop Won't Stop is the story of hip-hop, a generation-defining movement and the music that transformed American politics and culture forever. Hip hop is one of the most dominant and influential cultures in America, giving new voice to the younger generation. It defines a generation's worldview. Exploring hip hop's beginnings up to the present day, Jeff Chang and Dave "Davey D" Cook provide a provocative look into the new world that the hip hop generation has created. Based on original interviews with DJs, b-boys, rappers, activists, and gang members, with unforgettable portraits of many of hip hop's forebears, founders, mavericks, and present day icons, this book chronicles the epic events, ideas and the music that marked the hip hop generation's rise"--